Classical Antiquity in Serbian Legal Journals of the Second Half of the 19th and the Early 20th Century - Samardžić, Gligor M.; Aksentijević, Lazar D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper explores and documents all instances in which classical antiquity was referenced in Serbian legal journals during the second half of the 19th and the early 20th century. The analysis focuses on journals published within the territory of the Kingdom of Serbia, reflecting the prevailing social and ideological context of the period. Numerous allusions to classical antiquity were employed to reinforce interpretations and conceptualizations of the legal system. Authors frequently equated Athenian and Roman law with unwritten reasoning, natural law, or absolute law. The study examines how classical antiquity was perceived by these authors through a close reading of journal articles published in Pravda, Sudski list, Porota, Pravo, Pravnik, and Arhiv za pravne i društvene nauke.